The Influence of Local Wisdom-Based Inquiry Models on Problem Solving Skills - Habibi, Zohri; Syahidi, Khaerus; Wajdi, Badrul; Yusri, Ahmad; Munandar, Rizky (Indonesian Journal of Innovation in Education Research, 2025)
This study aims to determine whether there is an influence of the local wisdom-based inquiry model on students' problem-solving abilities in temperature and heat materials. The research method used is the Experimental method with Posttest-Only Control Design. Based on the results of data analysis, the t count value = 6.413 and t table = 1.697 with a significant rate of 5%. tcount > ttable then Ho is rejected so that it can be said that learning with the local wisdom-based inquiry model has an effect on students' problem-solving abilities in temperature and heat materials.